Pengaruh Fraud Diamond Terhadap Perilaku Fraud Academic dengan Student Behavior Sebagai Variabel Moderating - Murni, Mayang; Pratiwi, Henny (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The purpose of this study is to find out the effect of Diamond Fraud on academic fraud with student behavior as a moderating variable. The research method used was a quantitative research method by using questionnaire as data collection technique. The population of this study was all active students at Polytechnic LP3I Medan as many as 559 students. The sampling technique used saturated samples, which obtained a sample of 418 students.Â  The gathered data were analyzed by using descriptive statistic, multiple regression and moderating regression analysis. The result of this study showed that Diamond Fraud simultaneously affected academic fraud. However, partially the component of diamond fraud such as pressure, opportunity and rationalization had a significant effect on academic fraud, while the capability had no effect on fraud academic. Furthermore, the result of the moderating test were known that student behavior becomes a moderating variable between the influence of diamond fraud on academic fraud.